Caesarean delivery: Bringing more than just a bundle of joy. Issue 2 (15th July 2019) - Quinlan, Jane
ABSTRACT: Background : Chronic postsurgical pain (CPSP) is a potential complication of all surgical procedures, including caesarean delivery (CD). Psychological factors such as anxiety and depression with negative coping strategies are known to increase the risk of the development of CPSP. Aim : This short review will appraise some additional features that are unique to CD and assess the interplay between them and persisting pain. Methods : This is a narrative review with a focus on describing relevant features associated with the development of CPSP after CD. Results : Hormone changes, postpartum depression, breastfeeding, and sleep disturbance each may affect the mother's pain in the short and long term. Together they have the potential to negatively impact the mother–infant bond. Conclusions : In the weeks after delivery, pain, depression, and poor sleep negatively impact the mother's quality of life and her ability to care for, and bond with, her baby. This represents a critical time for the emotional, social, and behavioral development of the infant. Far-reaching benefits for the whole family may be realized by the early identification and management of persisting postoperative pain and postpartum depression.